On the role of atmospheric tides in the quiet-time variabilities of equatorial electrojet - Gurubaran, S.; Sathishkumar, S.; Veenadhari, B. (My University, 2016)
Simultaneous observations of geomagnetic field variations and upper mesospheric winds by MF radar from low latitudes spanning over a period of 19 years (1993-2011) are utilized in the present work to assess the role of upper atmospheric tides in causing the long-period variabilities of equatorial electrojet (EE J). Decomposition of ground magnetic data by adopting the method of natural orthogonal components (MNO C) (also referred to as the Principal Component Analysis (PCA))enables the separation of the normal quiet-time behaviour (the expected diurnal variation) and the abnormal (features like counter electrojet (CEJ)) field variation. Using the second principal component as a proxy for CEJ, we show in this work that the CEJs occur more frequently during the solar minimum years and a high degree of correlation is noticed between the enhanced tides during the solar minimum years and the occurrence of CEJs then.
Keywords: Atmospheric tides; EEJ; Equatorial electrojet; Geomagnetism; Equatorial Ionosphere